(untitled) (Conferencea, 2024)
Phraseological unities arise on the basis of a semantic shift in meaning. A new, phraseological meaning is created not as a result of a change in the meaning of individual components of a phrase, but by a change in the meaning of the entire complex. In phraseological unity, the individual meaning of the component words is absorbed and lost. This thesis learns translation studies of the phraseological units in the English and Uzbek languages with lexical and phraseological features.